Východiska bezpečnostního výzkumu ČR - Valášek, Jarmil; Linhart, Petr (Univerzita Pardubice, 2007)
Security situation has been changing in the world and in the territory as well, therefore it is necessary to create systematically new culture of safety which regards topical knowledge and experience. Capital assets into security research are necessary to rate as basic imput for the increase of the safety preparedness level of the Czech Republic. For these purposes it is desirable to develop security research that is able to produce ideas and technologies which will enable to sustain and renew the Czech Republic safety in changing conditions.

Security situation has been changing in the world and in the territory as well, therefore it is necessary to create systematically new culture of safety which regards topical knowledge and experience. Capital assets into security research are necessary to rate as basic imput for the increase of the safety preparedness level of the Czech Republic. For these purposes it is desirable to develop security research that is able to produce ideas and technologies which will enable to sustain and renew the Czech Republic safety in changing conditions.
Keywords: bezpečnostní výzkum; bezpečnost; Česká Republika; bezpečnostní opatření